Role of the Interplay between Spinodal Decomposition and Crystal Growth in the Morphological Evolution of Crystalline Bulk Heterojunctions - Ronsin, Olivier J. J.; Harting, Jens (Energy Technology, 2020)
The stability of organic solar cells is strongly affected by the morphology of the photoactive layers, whose separated crystalline and/or amorphous phases are kinetically quenched far from their thermodynamic equilibrium during the production process. The evolution of these structures during the lifetime of the cell remains poorly understood. Herein, a phase-field simulation framework is proposed, handling liquid–liquid demixing and polycrystalline growth at the same time to investigate the evolution of crystalline immiscible binary systems. It is found that initially, the nuclei trigger the spinodal decomposition, whereas the growing crystals quench the phase coarsening in the amorphous mixture. In contrast, the separated liquid phases guide the crystal growth along the domains of high concentration. It is also demonstrated that with a higher crystallization rate, in the final morphology, single crystals are more structured and form percolating pathways for each material with smaller lateral dimensions.
CRIS-Team Scopus Importer:2023-03-29
Keywords: crystallization; liquid–liquid demixing; organic solar cells; phase-field; stability